Estimates of the global, regional, and national burden of atrial fibrillation in older adults from 1990 to 2019: insights from the Global Burden of Disease study 2019 - Jiao, Min; Liu, Chenglin; Liu, Yongwen; Wang, Yan; Gao, Qianqian; Ma, Anning (Frontiers in Public Health, 2023)
Background: Atrial fibrillation (AF) is a predominant public health concern in older adults. The intention of our study was to further explore the global, regional, and national burden of AF in older adults aged 60-89 years between the years 1990 and 2019. Methods: The morbidity, mortality, disability-adjusted life years (DALYs) and age-standardized rates of AF were refined from the Global Burden of Diseases Study 2019. The epidemiological characteristics were assessed in numbers, age-standardized rates per 100,000 person-years and estimated annual percentage changes (EAPC). Results: Globally, a total of 33.31 million AF incident cases, 219.4 thousand deaths and 65.80 million DALYs were documented in 2019. There were no appreciable changes in EAPC from 1990 to 2019. The disease burden of AF differed significantly among territories and countries. At the national level, China presented the highest number of incident cases [818,493 (562871–1128695)], deaths cases [39,970 (33,722–46,387)] and DALYs [1383674 (1047540–1802516)]. In the global level, high body-mass index (BMI) and high systolic blood pressure (SBP) were the two leading hazard factors for the proportion of AF deaths. Conclusion: AF in the older adults remains a major public health concern all over the world. The burden of AF varies widely at both national and regional levels. From 1990 to 2019, the cases of incidences, deaths, and DALYs have showed a global increase. The ASIR, ASMR and ASDR have declined in the high-moderate SDI and the high SDI regions, however, the burden of AF increased promptly in the lower SDI regions. For high-risk individuals with AF, special attention should be paid to the main risk factors, controlling systolic blood pressure and body mass index within normal limits. Above all, it is necessary to illustrate the features of the global AF burden and develop more effective and targeted prevention and treatment strategies. Keywords: Atrial fibrillation; Older adults; Aging; Global Burden of Disease; Risk factors